The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4103/0971-4065.176145
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin and anti-hypertensive drugs in chronic kidney disease: Pharmacokinetic interactions and their clinical impact

Abstract: Patients on dialysis have an increased incidence of tuberculosis (TB). Rifampicin, a first-line antitubercular therapy (ATT) drug, is a potent inducer of hepatic cytochrome P450 (CYP). There is potential for pharmacokinetic interaction between rifampicin and anti-hypertensives that are CYP substrates: amlodipine and metoprolol. Therefore, hypertensive patients receiving rifampicin-based ATT are at risk for worsening of hypertension. However, this hypothesis has not yet been systematically studied. In this pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
1
15
0
4
Order By: Relevance
“…Prior publications have reported the hypertensive effect of tuberculosis treatment with rifampin, but all the studies involved patients with existing antihypertensive medications. [26][27][28][29][30] Thus, the BP-elevating effect is mostly explained by drug-drug interactions involving the PXR-mediated induction of drug metabolism and transport by rifampin. A study with patients requiring maintenance hemodialysis demonstrated dramatically lower concentrations of amlodipine, metoprolol, and prazosin after the start of rifampin-based antitubercular therapy with 46% of the 24 patients experiencing hypertensive crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Prior publications have reported the hypertensive effect of tuberculosis treatment with rifampin, but all the studies involved patients with existing antihypertensive medications. [26][27][28][29][30] Thus, the BP-elevating effect is mostly explained by drug-drug interactions involving the PXR-mediated induction of drug metabolism and transport by rifampin. A study with patients requiring maintenance hemodialysis demonstrated dramatically lower concentrations of amlodipine, metoprolol, and prazosin after the start of rifampin-based antitubercular therapy with 46% of the 24 patients experiencing hypertensive crisis.…”
Section: Discussionmentioning
confidence: 99%
“…The search of electronic databases resulted in 271 records in PubMed, 55 records in CNKI, and 60 records in WanFang, of which 39 were duplicates and 304 were not relevant. Within the remaining 43 records, seven studies were excluded on full‐text screening due to the lack of pharmacokinetic data, unreasonable discussion, recalculation of another study, or translation of a previous study 56–62 . As a result, 13 case reports, 20 pre‐post studies, and 3 cohort studies were included (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Within the remaining 43 records, seven studies were excluded on full-text screening due to the lack of pharmacokinetic data, unreasonable discussion, recalculation of another study, or translation of a previous study. [56][57][58][59][60][61][62] As a result, 13 case reports, 20 pre-post studies, and 3 cohort studies were included ( Figure 4).…”
Section: Literature Confirmationmentioning
confidence: 99%
“…Agrawal A et al . showed in 20 hypertensive dialyzed patients treated with amlodipine and rifampicin a reduction of more than 50% of plasma level of amlodipine in all patients reaching an undetectable level in 50%‐75% of patients.…”
Section: Case Reportsmentioning
confidence: 99%